TAFSIR AHKAM : : Logika Hukum Penetapan Kewajiban Nafkah dan Kadar Nafkah Perspektif Al-Qur’an dan Hadits - al amin, habibi (LPPM UNHASY, 2025)
The point of this research is to figure out the arguments for and against using legal logic in cases about alimony. The research method used is legal normative research. Data analysis employs the Ahkam interpretation method. The research data consists of Ahkam interpretations regarding maintenance, specifically: (Qs. An Nisa’:34), QS. At-Talaq[65]:6, (HR. Bukhari), (HR. An-Nasa’i and Ibn Majah). The results of this study conclude that the differences in legal logic in cases of alimony obligations and the amount of alimony between one school of thought and another are indicated by the differences in opinion between schools of thought, which simultaneously demonstrate the richness of Islamic fiqh methodology. Each imam, using their own framework of usul fiqh, interprets the primary sources (the Quran and Hadith) through different lenses, considering fiqh principles (such as custom, public interest, necessity, analogy), and sometimes prioritizing different principles, for example, the absolute protection of a wife's rights versus the ease for a husband facing economic difficulties. This is what shapes the pattern of legal reasoning and produces variations in legal rulings that remain within the bounds of Sharia, offering relevant alternative solutions for various conditions and eras.